Can Language be Planned? Sociolinguistic Theory for Developing Nations - Jernudd, Bjorn (University of Hawai'i Press, 2018)
This book is intended to serve several purposes: to demonstrate the need for a multidisciplinary approach to language planning, to awaken the interest of all the social sciences to the role of language in modernization, to interest social scientists in the theoretical gain to be had from the study of language planning, to help widen the field of sociolinguistics by interesting linguists in people's attempts to influence their own speech and the social and economic environment of deliberate language change, and to encourage participant language planners to scrutinize the processes that occur as they proceed to make and carry out language decisions. It is also meant to serve as a stimulus to research in language planning.